Stem cell therapies for periodontal tissue regeneration: A meta-analysis of clinical trials - Thuy-Duong; Bao-Hung; Thuy-T; Tung Nguyen-Thanh (Elsevier, 2023)
Objective: Stem cell therapy in periodontal tissue regeneration has reported optimistic regenerative results; evidence supporting its superiority over conventional methods is still ambiguous. Therefore, this meta-analysis aims to evaluate the therapeutic effects of stem cells in human periodontal regeneration. Design: A literature search was conducted to retrieve relevant articles on periodontal regeneration in stem cell therapy. A meta-analysis of the studies was conducted using the Stata software. Results: Fifteen studies that examined the effect of stem cell therapies on periodontal tissue regeneration in 369 patients were selected from databases. Regardless of the various types of cells, both odontogenic (periodontal ligament, dental pulp, gingiva stem cell) and non-odontogenic (bone marrow, periosteum-derived, and umbilical cord stem cells), the cell therapies witnessed significant improvements in terms of clinical attachment level (SMD, −0.67; 95CI, −0.90 to −0.43), probing depth (SMD, −0.76; 95% CI, −1.21 to - 0.31), radiographic intrabony defect depth (SMD, −0.87; 95% CI, −1.52 to −0.23), and histomorphometric analysis of mineralized bone (SMD, 0.80; 95% CI, 0.42 to 1.19) when compared to traditional without-cell treatment in patients. However, evidence on gingival recession, alveolar thickness gain, bone mineral density of bone core, and bone volume fraction of bone core outcomes did not reach statistical significance. Conclusions: Evidence suggests that the implementation of stem cell therapies in reconstructing compromised gingiva and alveolar bone tissue produces positive outcomes compared with conventional approaches. However, further well-designed investigations are needed to comprehensively identify the most effective source of cells and biomaterials for each case.